Analysis of Female Athlete Triad (FAT) Components: Energy and Nutritional Intake of Papuan Female Athletes - Sinaga, Evi; Wanena, Tery; Putra, Miftah Fariz Prima; Hidayat, Rodhi Rusdiyanto; Ibrahim, Ibrahim; Guntoro, Tri Setyo; Sinaga, Eva; Sinaga, Dewi Oktavia (Lambung Mangkurat University, 2024)
Female Athlete Triad (FAT) disrupts the health and performance of female athletes both in training and competition, leading to a decline in achievements. The purpose of this research was to analyze one of the components of the FAT namely energy availability in Papuan female athletes. This research is an observational study with a Mixed Methods approach, involving a total sample of 55 female Papua athletes in Jayapura, Papua. Energy and nutrient intake were conducted by collecting data on the energy and nutrient intake of Papuan female athletes through interview, 3x24 hour recalls and questionnaires. The demographic data of FAT risk factors collected include age, weight, height, injury history, and sports. The components of energy availability collected include eating disorders. Energy intake data were processed using the Nutrisurvey dietary intake data processing software. The data were then compared with the recommended adequacy and energy requirements for athletes. The average energy intake achievement in athletes was found to be 87% (2273.76 cal). The average carbohydrate intake was 288.14grs (77%). The average protein intake was 88.68grs (93.34%), while the average fat intake was 86.71grs (98%). Mostly athletes have fulfilled their energy and nutritional intake.